Designing An E-Education System In The University Of Mustansiriyah Baghdad, Iraq - Elameer , Amer Saleem Flayyeh (2011)
Designing an e-education system for UoMust (which would enhance learning opportunities for about 41000 individuals) was the main objective of this e-education research. Perekaan suatu sistem e-pendidikan untuk UoMust (yang dapat menambahbaik peluang pengajian kepada kira-kira 41000 individu) adalah objektif utama bagi penyelidikan e-pendidikan ini.